Iodine and mid-life women living in Auckland, New Zealand who avoid bread : a thesis presented in partial fulfillment of the requirements for the degree of Master of Science in Human Nutrition at Massey University, Albany, Auckland, New Zealand - Finlayson, Jacqueline (Massey University, 2019)
Aim: To investigate if avoidance of iodine fortified bread products by mid-life women results in low iodine status following mandatory fortification of bread with iodised salt in New Zealand in 2009. Method: This cross-sectional study actively recruited women whose consumption of iodine fortified commercially baked bread was less than one slice per day. Assessment of iodine intake and status was determined via food frequency questionnaire (FFQ), three-day diet diary (3DDD) and 24-hour urine collection. Urinary iodine concentration (UIC) was determined and daily urinary iodine excretion and daily iodine intake was assessed. Results: Forty-six mid-life women living in Auckland were recruited for assessment of dietary intake of iodine, women were aged between 40-63 years and did not have diagnosed thyroid disease. The median urinary iodine concentration was 49 (35, 78) μg/l and indicates deficiency (Zimmermann, 2011). The median urinary iodine excretion was 108 (74, 154) μg/day and based on these results, the estimated median iodine intake of 120 (82, 171) μg/day was determined. This intake is below the recommended dietary intake (RDI) of 150 μg/day. Further, 91% of participants’ intake was below the estimated average requirement (EAR) of 100μg/day. Conclusion: From this small sample, the study showed that mid-life women living in NZ who avoid bread are at risk of inadequate dietary iodine intake. This group is unable to benefit from the mandatory fortification of bread with iodised salt. This highlights the importance of continued monitoring of the iodine fortification programme within New Zealand. Further research should investigate both thyroid function and dietary habits of low bread consumers in New Zealand in a larger sample. Also an attempt to raise awareness of the best sources of iodine in the NZ diet, to improve both dietary intake and status of iodine amongst at-risk groups such as this is highly recommended.
Keywords: Middle aged women; Nutrition; Requirements; New Zealand; Iodine; Enriched foods; Bread; 321004 Nutritional science